Market capacity and consumer behaviour from logistic analysis view - Koltan, Nadežda Doronina; Girdzijauskas, Stasys; Štreimikienė, Dalia (Technological and Economic Development of Economy, 2013)
The paper deals with market capacity and the integral parts of it. One of the most critical consisting parts of the market's capacity are market niches, the fulfilment of which depends on market openness or closeness. In the opened market there is a possibility of reproduction, while for the closed market the saturation is more typical. However, reproduction and saturation have one similar feature: both influence the beginning of a crisis. The main difference between reproduction and saturation is in reproduction's possibility to create a new market niches driven by globalization, innovation and the growth of the living standards of population. A creation of the new market niche in case of saturation is not possible because of the consumers’ expectations. The return on investments in the closed market is growing exactly at the moment when the market niche approaches zero. At the same time people tend to invest into this market with a hope to get the highest profits. This finally leads to the bubble formation. The paper aims to define the main factors influencing markets’ niches saturation and seeks to apply logistical capital theory for assessment of market saturation level for the prediction of forthcoming economic crisis.